Pelaksanaan Pembelajaran Seni Budaya (Tari) Kelas X SMAN 9 Padang - Rima Salsabila; Tulus Handra Kadir (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This study aims to describe and find out the implementation of learning basic motion techniques in class X of SMA Negeri 9 Padang. This type of research is qualitative research with a descriptive method of analysis. The research instruments are the researchers themselves and are assisted by supporting instruments such as stationery, cameras and recorders. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, identifying data, clarifying data and concluding data. The results of the study show that cultural arts learning in the school has not been effective due to the lack of appropriate use of learning media, especially in the context of dance art. The use of only videos as a learning medium and group discussion methods only provide a limited picture of the material being studied. It is important to increase students' enthusiasm and motivation by providing a clear understanding of what is being learned and the purpose of learning cultural arts. Although art is a creative field of study, learning also has specific goals, such as developing the potential of artists who can contribute to different levels of education, including from the secondary and elementary levels.